Uraemia-induced immune senescence and clinical outcomes in chronic kidney disease patients. Issue 4 (6th September 2018) - Crépin, Thomas; Legendre, Mathieu; Carron, Clémence; Vachey, Clément; Courivaud, Cécile; Rebibou, Jean-Michel; Ferrand, Christophe; Laheurte, Caroline; Vauchy, Charline; Gaiffe, Emilie; Saas, Philippe; Ducloux, Didier; et al.
Abstract: Background: Patients with chronic kidney disease (CKD) are more prone to develop premature age-related diseases. Data on immune senescence are scarce in CKD populations, except in end-stage renal disease and dialysis. We designed a longitudinal prospective study to evaluate immune senescence at different CKD stages and its influence on CKD patient outcomes. Methods: Clinical and biological data collections were performed on 222 patients at different CKD stages [1–2 ( n = 85), 4 ( n = 53) and 5 ( n = 84)]. Immune senescence biomarkers were measured by cytometry on T cells (CD28, CD57, CD45RA, CD31, γH2A.X) or by quantitative polymerase chain reaction [relative telomere length (RTL)] on peripheral blood mononuclear cells and analysed according to CKD stages and outcomes. Results: CKD was associated with an increase in immune senescence and inflammation biomarkers, as follows: low thymic output (197 ± 25 versus 88 ± 13 versus 73 ± 21 CD4 + CD45RA + CD31 + T cells/mm 3 ), an increased proportion of terminally differentiated T cells (CD8 + CD28 − CD57 + ) (24 ± 18 versus 32 ± 17 versus 35 ± 19%) restricted to cytomegalovirus-positive patients, telomere shortening (1.11 ± 0.36 versus 0.78 ± 0.24 versus 0.97 ± 0.21 telomere:single copy ratio) and an increase in C-reactive protein levels [median 2.9 (range 1.8–4.9) versus 5.1 (27–9.6) versus 6.2 (3.4–10.5) mg/L]. In multivariate analysis, shorter RTL was associated with death hazard ratio [HR] 4.12 [95% confidence interval (CI) 1.44–11.75]. Low thymic output was associated with infections [HR 1.79 (95% CI (1.34–9.58)] and terminally differentiated CD8 + T-cell expansion with a risk of cardiovascular events [CEs; HR 4.86 (95% CI 1.72–13.72)]. Conclusion: CKD was associated with premature immune ageing. Each of these alterations increased the risk of specific age-related diseases, such as RTL and death, thymic function and infections and terminally differentiated CD8 + T-cell expansion and CEs.